Log in to add a comment

Log in to add a comment

Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.

velocity = distance traveled / time taken v = s/t => s= vt

If u is the initial velocity of an uniformly accelerating body and v is its velocity after a time t, then since the acceleration is UNIFORM, we can find the average velocity of the body as follows average velocity = (u+v)/2 Now, the distance s, traveled in the time t by the body is given by distance traveled = average velocity x time s = [(u+v)/2]t From eq 1 we have v=u+at, substituting this in the above equation for v, we get s = [(u+u+at)/2]t => s = [(2u+at)/2]t => s = [(u + (1/2)at)]t => s = ut + (1/2)at2 ; This is our 2nd eq of motion

We start with squaring eq 1 Thus we have v2 = (u+at)2 => v2 = u2 + a2t2 + 2uat => v2 = u2 + 2uat + a2t2 => v2 = u2 + 2a(ut + (1/2)at2) now, using eq 2 we have => v2 = u2 + 2as

That was the third eq of motion.

HOPE THAT IT HELPED YOU...